Factors Affecting the Spread of Narcotics in Simpang Dolok Village, Datuk Fifty District, Batubara Regency - Anisa Sufia Sopang; Muhammad Rusdi; Fahmi Zahary; Fikri Aditiya Sitorus; Noor Azizah (Universitas Ibn Khaldun Bogor, 2023)
Narcotics abuse is a serious problem that affects society in various countries. This research focuses on identifying factors that contribute to the spread of narcotics in Simpang Dolok Village, a rural area in Batu Bara Regency. The research results highlight the importance of social and economic inequality, high levels of poverty, and the easy availability of narcotics in driving the spread of narcotics. Social factors, including peer pressure, also influence young people in this village to try narcotics. Apart from that, low public awareness about the dangers of narcotics, especially among the less educated, also supports the situation. Handling the problem of the spread of narcotics in Simpang Dolok Village requires a holistic approach that includes economic empowerment, stronger law enforcement, and better education programs about the risks of narcotics. Close cooperation between government, society, and other stakeholders is needed to overcome this problem. This research provides an in-depth understanding of the factors that influence the spread of narcotics at the village level, guiding more effective prevention and control efforts in Simpang Dolok Village and the surrounding area.